2005
DOI: 10.1002/adma.200401115
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Signal‐Enhancing Self‐Assembled Coating for Endovascular Devices

Abstract: tor was submerged in a thermostated water bath and stirred at 250 rpm. After 20 min, the homogeneous mixture of methyl methacrylate, vinylcarbazole, the oxadiazole derivative (NDA), and the perylene was poured into the reactor and stirred vigorously. The mixture was allowed to polymerize at 70 C for 7 h. Sodium bicarbonate and sodium persulfate were dissolved in water and added to the reaction mixture. The product was filtered and washed with DDI water. A standard recipe for emulsion copolymerization is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Degradable polyelectrolyte microcapsules made of polypeptides and/-or polysaccharides were reported recently. [9,10] As polyelecrolyte multilayers on planar substrates start to emerge as multifunctional delivery platforms for implants, e.g., drug eluting stents or dental implants, [11][12][13][14][15][16][17][18][19][20] the potential of polyelectrolyte microcapsules as drug delivery systems could increase. [6,21] Polyelectrolyte microcapsules have the advantages of mild preparation conditions, multifunctionality, and the capacity to encapsulate large amounts of material.…”
Section: Introductionmentioning
confidence: 99%
“…Degradable polyelectrolyte microcapsules made of polypeptides and/-or polysaccharides were reported recently. [9,10] As polyelecrolyte multilayers on planar substrates start to emerge as multifunctional delivery platforms for implants, e.g., drug eluting stents or dental implants, [11][12][13][14][15][16][17][18][19][20] the potential of polyelectrolyte microcapsules as drug delivery systems could increase. [6,21] Polyelectrolyte microcapsules have the advantages of mild preparation conditions, multifunctionality, and the capacity to encapsulate large amounts of material.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive work has shown that it is possible to reduce scanning time with the help of parallel imaging methods [16,17], that a substantial improvement in the SNR is available through multi-channel coils [18], and that larger area can be examined using traveling-wave technique [19,20]. The second approach is based on the idea to employ special contrast agents [21] locally enhancing the magnetic field, such as rare-earth magnetic atoms [22] and magnetic nanoparticles [23]. The third approach relies on special additional pads placed near the object.…”
mentioning
confidence: 99%
“…[22] However, because of the large amount of carboxy groups on the dendrimer surface, the Fe 3 O 4 NPs modified with FA do not show specific binding to the FAR-expressing cells in vitro. In a previous work, it has been shown that Fe 3 O 4 NPs modified through an approach that combines a layer-by-layer (LbL) self-assembly technique [23][24][25][26][27][28][29][30][31][32][33][34] and dendrimer chemistry [18][19][20] can specifically target tumor cells overexpressing FAR in vitro. [35] In these studies, a bilayer composed of polystyrene sulfonate sodium salt (PSS) and FAand FI (fluorescein isothiocyanate)-functionalized PAMAM dendrimers of generation 5 (G5.NH 2 -FI-FA) were assembled onto Fe 3 O 4 NPs through electrostatic LbL assembly, followed by acetylation of the remaining surface amine groups of the assembled G5 dendrimers.…”
mentioning
confidence: 99%